Effects of γ-butyrobetaine and l-carnitine on carnitine concentrations in various muscle tissues of finishing pigs - J M Benz; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
The primary method of L-carnitine production, similar to the biological process that occurs in the liver and kidneys, is from microbial fermentation of Î³-Butyrobetaine. Therefore, the objective of this study was to see if supplementing the diet with Î³-Butyrobetaine would increase organ and muscle tissue carnitine concentrations. One-hundred-twenty-five barrows were fed diets containing either L-carnitine (100 ppm), Î³-Butyrobetaine (100 ppm) or a combination of L-carnitine (50 ppm) and Î³-Butyrobetaine (50 ppm). The addition of L-carnitine, Î³-Butyrobetaine and the combination of L-carnitine and Î³-Butyrobetaine increased (P<0.01) free carnitine concentration in the longissimus, diaphragm, and heart. L-carnitine and the combination of L-carnitine and Î³-Butyrobetaine increased (P<0.01) free carnitine concentration in the kidney. Therefore, these results suggest that Î³-Butyrobetaine and/or L-carnitine can be used to increase carnitine concentrations of organ and muscle tissues.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Vitamins; L-carnitine; Î³-Butyrobetaine